RHOBTB2 Variant p.Arg511Gln Causes Developmental and Epileptic Encephalopathy Type 64 in an Infant: A Case Report and Hotspot Variant Analysis - Qian Liu; Feifei Li; Qin Ruan; Nana Wang; Zhengjun Fan (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Developmental and epileptic encephalopathies (DEEs) are a heterogeneous group of brain disorders. Variants in the Rho‐related BTB domain‐containing 2 gene (RHOBTB2) can lead to DEE64, which is characterized by early‐onset epilepsy, varying degrees of motor developmental delay and intellectual disability, microcephaly, and movement disorders. More than half of the variants are located at Arg483 and Arg511 within the BTB domain; however, the underlying mechanism of action of these hotspot variants remains unexplored. Methods We performed whole‐exome and Sanger sequencing on the patient and his parents. We collected recurrent variant information from the literature on RHOBTB2 variants. We used Discovery Studio software to analyze the folding free energy of variant proteins, and the AlphaFold database to analyze structural alterations in mutant proteins. Results The patient presented with early‐onset epilepsy, developmental delay, and brain structural abnormalities. Genetic analysis revealed a de novo variant in RHOBTB2, c.1532G>A, p.(Arg511Gln). To date, 60 cases of DEE patients with RHOBTB2 variants have been reported, with approximately 50% of variants located at Arg483 and Arg511. Among them, p.Arg511Gln, p.Arg483His, and p.Arg511Trp have an incidence rate exceeding 10%. The folding free energy of these high‐frequency variants proteins is reduced, which may lead to increased structural stability. Conclusion This study highlights the importance of RHOBTB2 hotspot variants in DEE64 and provides insights into their potential mechanisms of action. We recommend RHOBTB2 gene testing for patients with relevant clinical manifestations to facilitate precise diagnosis and treatment of DEE.